2019
DOI: 10.1007/s00392-019-01575-y
|View full text |Cite|
|
Sign up to set email alerts
|

One-year clinical outcomes in patients with renal insufficiency after contemporary PCI: data from a multicenter registry

Abstract: Background Chronic kidney disease (CKD) is highly prevalent in patients with coronary artery disease (CAD). Objective The outcome following revascularization using contemporary technologies (new-generation abluminal sirolimuseluting stents with thin struts) in patients with CKD (i.e., glomerular filtration rate of < 60 mL/min/1.73m 2 ) and in patients with hemodialysis (HD) is unknown. Methods e-Ultimaster is a prospective, single-arm, multi-center registry with clinical follow-up at 3 months and 1 year. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
(61 reference statements)
0
24
0
1
Order By: Relevance
“…CKD patients are more prone to IHD and tend to have poorer outcomes following revascularization with PCI or coronary artery bypass surgery [8,22]. Even in the era of PCI with the newer generation of DES, and with wellbalanced guideline-based medical therapy, adverse cardiovascular outcomes are more frequent in those with than without CKD [10,19,23]. Additionally, higher rates of MACE were recently reported in patients on hemodialysis who underwent PCI with DEB compared to patients not on hemodialysis [24].…”
Section: Discussionmentioning
confidence: 99%
“…CKD patients are more prone to IHD and tend to have poorer outcomes following revascularization with PCI or coronary artery bypass surgery [8,22]. Even in the era of PCI with the newer generation of DES, and with wellbalanced guideline-based medical therapy, adverse cardiovascular outcomes are more frequent in those with than without CKD [10,19,23]. Additionally, higher rates of MACE were recently reported in patients on hemodialysis who underwent PCI with DEB compared to patients not on hemodialysis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the applied definition, the prevalence of small vessel disease (SVD) reaches roughly 1/3 of patients with symptomatic coronary artery disease (CAD) [1,2], especially patients with chronic kidney disease (CKD) [3], diabetes mellitus [4], and active smokers [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical profile of SVD patients, as well as higher rate of short-and long-term procedural complications, translates into poor long-term outcomes [3,5]. Despite the use of new-generation drug-eluting stents (DES), an accumulating body of evidence suggests that PCI of coronary arteries < 2.5 mm is associated with a high rate of target lesion failure or cardiovascular death [5].…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, overall-mortality was higher in patients with more advanced CKD than in patients without CKD. Several studies with follow-up periods of 1–5 years support this observation: a very recent international, multicenter registry evaluation on the outcome after contemporary PCI in patients with CAD and renal insufficiency reported that one of the most powerful parameters for adverse outcome, namely major adverse cardiovascular events including cardiac death as well as a patient-oriented composite endpoint including all-cause death, was the presence of CKD and dialysis-dependent CKD [ 36 ]. Other predictors were age, diabetes mellitus, previous MI, and smoking, all in good accordance with our findings.…”
Section: Discussionmentioning
confidence: 99%